Flexible scorpionates for transfer hydrogenation: The first example of their catalytic application - Tsoureas, Nikolaos; Owen, Gareth R.; Hamilton, Alex; Orpen, A Guy (Dalton Transactions, 2008)
Rhodium and iridium complexes of flexible scorpionate ligands based on azaindole were synthesised in good yields. The complexes were characterised in solution and in the solid state. Structural characterisation revealed a B-H-metal interaction, which is retained in solution. Given the greater flexibility of the ligand and potential cooperative effect of boron, the complexes were tested for their activity in the transfer hydrogenation of ketones. © 2008 The Royal Society of Chemistry.